Design Analysis and Fabrication of Microstrip Patch Antennas for Various Applications Using Electromagnetic Bandgap and Defected Ground Structures - Mittal, Nitika (My University, 2015)
In an era of increasing mobility, there is a necessity that people communicate with each other irrespective of the location or information of the individuals. Wireless communication plays a critical role in this regard. The rise in demand of wireless communication has paved the way for better comprehension of cardinal issues in electromagnetic and communication theory. In various wireless communication system, a significant role in making the system reliable and elevating its performance is played by a device known as ‘antenna’. The use of wireless communication is not omissible in the present era. Microstrip antennas have been utilised broadly in various fields such as in satellite communications, aerospace, radars, biomedical applications and reflector feeds, as a result of their benefit of a low profile, light weight and affinity with integrated circuits. Nevertheless, they go through from disadvantages for example narrow bandwidth; low gain and excitation of surface waves, appreciable return loss etc. All the above mentioned drawbacks have restricted their functions in various fields. In order to swamp the drawbacks of bandwidth of microstrip antennas, many approaches have been developed. Because of above mentioned reasons, new techniques are still being probed, and electromagnetic band gap materials, as antenna substrates, have captivated consideration. The ever growing requirement for low profile wireless communication antennas resulted to probe of artificial structures with distinguishing electromagnetic characteristics. Amid they are the man-made metamaterial, electromagnetic band gap structures (EBG), high impedance surfaces (HIS), and defected ground structure (DGS). In this work represented, Transmission line model is utilised to simulate rectangular Microstrip Patch Antenna with the help of microstrip centre feed line. The aim is improvement of the antenna parameters like bandwidth, surface wave suppression, gain, efficiency, and high return loss etc. using new EBG and DGS structures. The radiating patch can have any structure like rectangular, circular, disc shaped, cylindrical etc. but rectangular is favoured. The structural design includes selection of the patch, slots width and dimensions of EBG and DGS structures are the major specifications along with the feed line depth.In this thesis report various antenna designs are presented and studied various effects of different specifications for example length and width of patch, height of substrate, dielectric constant EBG and DGS parameters for WLAN, DBS and RF portable devices applications. The antennas are designed using CST 10 microwave studio.
M.E. (ECED)
Keywords: Electromagnetic BandGap (EBG); Microstrip Patch Antenna (MPA); Defected Ground Structure (DGS); Direct Broadcast Satellite (DBS) application; Slotted Antenna; RF Portable Devices; Electronics and Communication; Electronics